2005
DOI: 10.1111/j.1475-097x.2004.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability in young patients with diabetes mellitus and healthy subjects explored by Poincaré and sequence plots

Abstract: Autonomic neuropathy is a common complication of the diabetes mellitus (DM). The significance of its early diagnosis is very high because the mortality of the patients with this complication is elevated. Considering the effort to apply new mathematical methods to cardiac dysregulation diagnosis, the major aim of the study was to ascertain which of the new heart rate variability (HRV) parameters are different in young patients with DM type 1 compared with control group. The next aim was to assess the HRV change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
33
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 42 publications
6
33
0
Order By: Relevance
“…On the contrary a large HRV is a favourable prognostic in the decrease of disorder incidence for apparently healthy men (Molgaard et al 1991) or in the advancement of disease for patients (Hayano et al 1991). Likewise, low HRV in childhood is associated with several paediatric issues such as congenital heart diseases (Massin and von Bernuth 1998), obesity (Gutin et al 2000) or diabetes (Javorka et al 2005). Moreover, the decrease of the HRV is coupled with the worsening of the disease (Gutin et al 2000;Javorka et al 2005).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…On the contrary a large HRV is a favourable prognostic in the decrease of disorder incidence for apparently healthy men (Molgaard et al 1991) or in the advancement of disease for patients (Hayano et al 1991). Likewise, low HRV in childhood is associated with several paediatric issues such as congenital heart diseases (Massin and von Bernuth 1998), obesity (Gutin et al 2000) or diabetes (Javorka et al 2005). Moreover, the decrease of the HRV is coupled with the worsening of the disease (Gutin et al 2000;Javorka et al 2005).…”
Section: Introductionmentioning
confidence: 95%
“…Likewise, low HRV in childhood is associated with several paediatric issues such as congenital heart diseases (Massin and von Bernuth 1998), obesity (Gutin et al 2000) or diabetes (Javorka et al 2005). Moreover, the decrease of the HRV is coupled with the worsening of the disease (Gutin et al 2000;Javorka et al 2005).…”
Section: Introductionmentioning
confidence: 98%
“…For example, a cigar-shaped plot along the principal diagonal (x ϭ y) would reveal high autocorrelation within the time series, while a circular plot would reveal periodicity (the Poincaré plot of a sine wave or a pendulum is a circle). The Poincaré plot has been used extensively to describe heart rate variability [15][16][17][18][19] and was also introduced to the analysis of CGM time series. 20 In this paper, we propose an altered Poincaré-type plot, which extends the visualization of system dynamics to depiction of the co-dynamics of BG and CGM.…”
mentioning
confidence: 99%
“…This study showed "the effect of metabolic memory" where each period of worsened compensation can negativelly influence the prognosis of the diabetic patient. Some studies with lower number of patients did not confirm the association between diabetes compensation and chronic complications (M. Javorka et al, 2005).…”
Section: Risk Factorsmentioning
confidence: 99%
“…The biggest study aimed at chronic diabetic complications, EURODIAB IDDM Complication Study, confirmed the significant correlation between glycosylation hemoglobin level and cardiovascular neuropathy. Even some authors denied this relation (M. Javorka et al, 2005), the optimal glycemia maintenance is strongly recommended as a prevention of diabetic complication origin. Children diabetic patients are treated by intensified insulin regimen.…”
Section: Euglycemia Maintenancementioning
confidence: 99%